Determinan Niat Untuk Menggunakan Uang Elektronik Syariah : Integrasi TAM dengan Persepsi Religiusitas - Diana Nabilatul Arifah; Sulistya Rusgianto (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The benefits of a transaction can be seen from how the payment system runs efficiently by using the minimum possible cost. the use of e-money is growing very rapidly in Indonesia, but the use of Islamic electronic money is still low. research that can identify factors that have the possibility to influence consumer intention to use electronic money or sharia e-money so as to increase its use in Indonesia. In this study, researchers want to integrate the Tecnology Acceptence model or commonly called TAM which is considered a simple model but has a strong role in predicting and explaining behavioral acceptance intentions with perceived religiosity. this study also considers knowledge of Riba (KR) as a moderating variable that can weaken and streng then the intention to use Islamic e-money which has not been considered by many other studies. The method used quantitative method with 172 samples with data analysis techniques using structural equation modelling (SEM). This study found that the integration of the TAM model and perceived religiosity (PR) can explain the intention to use Sharia electronic money (INT) by 60%. SN, PEU, PR have a significant effect on INT, while PU has no significant effect on INT. KR can also moderate the relationship between SN and INT